Advances, Challenges, and Perspectives for Heavy‐Metal‐Free Blue‐Emitting Indium Phosphide Quantum Dot Light‐Emitting Diodes. Issue 4 (9th December 2022) - Cui, Zhongjie; Yang, Dan; Qin, Shuaitao; Wen, Zhuoqi; He, Haiyang; Mei, Shiliang; Zhang, Wanlu; Xing, Guichuan; Liang, Chao; Guo, Ruiqian
Abstract: Quantum dot light‐emitting diodes (QLEDs), regarded as promising candidates in the next‐generation display, have attracted much attention recently. In spite of the outstanding performance of cadmium‐based (Cd‐based) QLEDs, the toxicity of Cd hinders their wide application. Indium phosphide quantum dots (InP QDs) with heavy‐metal‐free feature and competitive performance are considered to be able to replace Cd‐based QDs as emitting layer in the QLEDs. Much progress is obtained in the red‐emitting and green‐emitting InP‐based QLEDs. However, the blue‐emitting ones are faced with great challenges and are demanded on full‐color display urgently, which is limited by the inferior performance of blue‐emitting InP QDs and lack of investigations about their QLED devices. In this review, the encountered challenges for high‐quality blue‐emitting InP QDs are presented. Common strategies for blue‐emitting InP QDs, including size engineering, composition engineering, and surface engineering are presented and analyzed. The progress of blue‐emitting InP‐based QLEDs, which strongly relies on the advances of materials, is also summarized. Finally, some perspectives from device physics are provided and discussed to inspire more efficient strategies toward blue‐emitting InP‐based QLEDs. Abstract : This review focuses on the challenges and strategies for heavy‐metal‐free blue‐emitting indium phosphide quantum dots (InP QDs). It is pointed out that the advances of blue‐emitting InP QDs have decided the development of corresponding QD light‐emitting diodes (QLEDs) by now. Moreover, the challenges for blue‐emitting InP‐based QLEDs and some perspectives from the insight of device physics are provided.